Fibromyalgia as a Predictor of Increased Postoperative Complications, Readmission Rates, and Hospital Costs in Patients Undergoing Posterior Lumbar Spine Fusion. Issue 4 (15th February 2019) - Donnally, Chester J.; Vakharia, Rushabh M.; Rush, Augustus J.; Damodar, Dhanur; Vakharia, Ajit J.; Goz, Vadim; Lebwohl, Nathan H.
Abstract : Study Design: Retrospective review. Objective: The aim of this study was to identify whether a concomitant diagnosis of fibromyalgia (FM) influences postoperative complications, readmission rates or cost following primary 1 to 2 level lumbar fusions in an elective setting. Summary of Background Data: Patients with FM often are limited by chronic lower back pain, many of whom will seek operative treatment. No previous study has evaluated whether patients with a concomitant diagnosis of FM have more complications following spine surgery. Methods: Medicare data (2005–2014) from a national database was queried for patients who underwent primary 1 to 2 level posterolateral lumbar spine fusion for degenerative lumbar pathology. Thirty- and 90-day postoperative complication rates, readmission rates, and treatment costs were queried. To reduce confounding, FM patients were matched with a control cohort of non-FM patients using patient demographics, treatment modality, and comorbid conditions, and then analyzed by multivariable logistic regression. Results: Within the first 30-day postoperative, acute post hemorrhagic anemia (odds ratio [OR]: 2.58; P < 0.001) and readmission rates were significantly higher in FM patients compared to controls. There was no significant difference in wound related complications within first 30-days (0.19% vs. 0.23%; P = 0.520) or with length of stay (3.60 vs. 3.53 days; P = 0.08). Within 90-day postoperative, FM patients had higher rates of pneumonia (OR: 3.73; P < 0.001) and incurred 5.31% more in hospital charges reimbursed compared to the control cohort. Conclusion: Primary 1 to 2 level lumbar fusions performed on FM patients have higher rates of postoperative anemia, pneumonia, cost of care, and readmission compared to match controls. FM patients and surgeons should be aware of these increased risks in an effort to control hospital costs and potential complications. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textFibromyalgia (FM) is a diagnosis that physicians are continuing to better understand. Compared to patients without a concomitant diagnosis of FM, those with FM have higher incidences of post-operative complications ( i.e., pneumonia and anemia), readmission rates, and hospital costs of care after undergoing primary 1 to 2 level lumbar fusions.